Description of the Truck Drivers’ Knowledge, Attitudes and Practices in Preventing Sexually Transmitted Infection at Transportation Service Provider in Bandung 2013 - Novianti, L L (KnE Life Sciences, 2019)
Sexually transmitted infections (STIs) and its complications are one of the health problems increasingly alarming. The truck drivers were one of the groups who are risky of carrying or being infected by STIs. They also identified as a group that improperly performed STIs prevention activities. Therefore, it is essential to determine their knowledge, attitudes, and practices related to STIs prevention. This descriptive study aimed to describe the truck drivers’ knowledge, attitudes, and practices in preventing STIs transmission. Fifty-one respondents were recruited using total sampling technique. Data were collected using questionnaires, and collected data were analyzed using descriptive statistic, frequency dan percentage. The result showed there were 23 (45.10 %) respondents who had sufficient knowledge, 29 (56.86%) respondents reported hostile attitudes and 26 (50.98%) respondents who performed bad practices. Regarding knowledge, there were two items with the lowest score including wearing condoms and myths. In STIs practices, searching for information and wearing condoms there were two aspects with lowest scores. Thus it is recommended for nurses in the community level to improve their efforts in enhancing truck drivers’ knowledge and attitude, particularly in using a condom, how HIV transmitted and correcting the myth-related STIs. Keywords: Sexually transmitted infections; truck driver; prevention